Exfoliative Cytological Changes in Peritoneal Fluid from Patients on Peritoneal Dialysis - Kattab, Yarub I.; Al-Qazzaz, Mutaz A.; Mousa, Liqaa R. (AL-Kindy College Medical Journal, 2008)
Background: Ambulatory peritoneal dialysis introduced by Popvich et al (13) in 1978 , consists of a four to five hours lavage of peritoneal cavity with 2000 ml of glucose solution .It remains a useful method for treating patients with end stage renal failure till renal transplantation becomes possible. Objectives: The aim of the study is to evaluate the value of cytological changes of mesothelial cells in dialysate patients. Methods: Within one year period, 32 cytological peritoneal fluid samples were collected from patients with end stage renal failure regardless of the underlying causes, admitted to the dialyzing unit in Kadimya Teaching Hospital. Smears were prepared and fixed in 95 % ethyl alcohol and then stained with H & E stain to be interpreted by the same pathologist. Results: Thirty two samples of peritoneal fluid were obtained from patients in peritoneal dialysis with a mean age of 54.8 years and male to female ratio of about 1.9: 1. Twenty two had short term dialysis were compared with 10 patients with long term dialysis. Gross examination of the samples revealed clear yellow fluid. Macroscopical examination showed no evidence of inflammatory cells with increased exfoliation, cellularity and three dimensional mesothelial cellular clustering pattern with increased nuclear size. No statistical significances were found in the changes seen in cytological smears between both groups but remarkable nuclear changes were shown in both of them. Conclusion: This study demonstrated that peritoneal dialysis of any duration can induce significant atypical changes in mesothelial cells. The pathologist needs to be aware of these changes and to include peritoneal dialysis in the list of other benign conditions that cause reactive mesothelial atypia